An experimental investigation of uncoated WC-Co tool life and wear in turning of stainless steel / Nur Affatin Zawawi - Zawawi, Nur Affatin (2016)
Stainless steel is one of the most popularly engineering materials with wide variety of applications. Stainless steel is iron-base alloys containing 10.5 percent or more chromium, which acts as inhibitor from getting corroded. In addition, stainless steel is known as high ductility and weldability material. However, stainless steel is having low machinability due high built-up edge (BUE) formation, high work hardening and low heat conductivity which consequently contributed to poor surface quality and rapid tool wear. In the present work, the machinability of stainless steel is studied using uncoated WC-Co cutting tool in turning process. Three levels of rotational speed (N) with constant feed rate (f) and depth of cut (d) were investigated toward tool wear, tool life and surface roughness. The wear mechanism will be examining using Scanning Electron Microscope (SEM) while the tool life calculated based on VB length. The surface roughness was measured by Portable Surface Roughness Machine. The result showed that the tool wear is increased with the increasing of speed. Similarly, the tool life decreased as the cutting speed increased. The surface roughness is decreased as the cutting speed increased. Flank wear and crater wear are main wear mechanisms in this experiment. Flank wear is mainly occurred on the flank side that attributed to the rubbing action of edge tool along the machined work piece. Meanwhile, the crater wear was observed on the rake face due to diffusion wear mechanism. These results shown that the cutting speed in machining is mainly impacts the surface finish and tool wear.